Pengembangan E-Modul Projek Berbasis Kearifan Lokal Sabilulungan Untuk Membangun Karakter Peduli Lingkungan - Hanifah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The environmental crisis in Bekasi Regency, such as flooding and high waste production, requires educational solutions based on environmental character. This research aims to develop an e-module project based on the local wisdom of Sabilulungan for elementary school students, using a Project-Based Learning (PjBL) approach and digital technology. The ADDIE Research and Development (R&D) method was used through five stages: teacher needs analysis, module design based on Google Sites and Canva for Education, trials at SDN Pasirsari 03, and holistic evaluation. Expert validation results showed high feasibility (94% technology experts, 93% environmental experts). The implementation of this e-module significantly increased student engagement: cognitive (50%→89%), affective (45%→84%), and behavioral (59%→90%). In addition, this e-module succeeded in reducing school waste by 15% and strengthening school-community collaboration through the Sabilulungan Festival. The advantages of this innovation lie in the integration of local values and the flexibility of adaptation to other regions. The implications of this research encourage adoption by policy makers with teacher training and replication guidelines based on local wisdom.